2016
DOI: 10.32601/ejal.460988
|View full text |Cite
|
Sign up to set email alerts
|

The effects of accessing L1 versus L2 definitional glosses on L2 learners’ reading comprehension and vocabulary learning

Abstract: This study was conducted to investigate the effects of different types of glosses and no-gloss condition on second language vocabulary learning. There were totally 81 high school students involved in the study, and they were randomly divided into three groups: L1-gloss group, L2-gloss group, and No-gloss group. These three groups were subjected to three main tests: reading comprehension test, immediate vocabulary test, and delayed vocabulary test. They were also asked to complete a student opinion questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…A possible explanation for the results of this study is that glossing difficult vocabulary helps learners acquire their meaning. This was proved by some studies (e.g., Al-Ghafli & Hussain, 2011;Arpaci, 2016;Azari, 2012;Azari, Abdullah, Heng, & Hoon, 2012a;Ghabanchi & Ayoubi, 2012;Ghahari & Heidarolad, 2015;Huang, 2010;Jung, 2016;Ko, 2012;Salehi & Naserieh, 2013;Todd, 2014;Tong, 2017;Zhao & Ren, 2017). This also goes along with Barcroft's (2015) belief that activities which introduce the meanings of words to learners in the early phase of learning the words enhance the acquisition of word meanings.…”
Section: Discussionmentioning
confidence: 66%
“…A possible explanation for the results of this study is that glossing difficult vocabulary helps learners acquire their meaning. This was proved by some studies (e.g., Al-Ghafli & Hussain, 2011;Arpaci, 2016;Azari, 2012;Azari, Abdullah, Heng, & Hoon, 2012a;Ghabanchi & Ayoubi, 2012;Ghahari & Heidarolad, 2015;Huang, 2010;Jung, 2016;Ko, 2012;Salehi & Naserieh, 2013;Todd, 2014;Tong, 2017;Zhao & Ren, 2017). This also goes along with Barcroft's (2015) belief that activities which introduce the meanings of words to learners in the early phase of learning the words enhance the acquisition of word meanings.…”
Section: Discussionmentioning
confidence: 66%
“…The review of the literature revealed that many studies tackled the issue of classroom CS from various aspects (Arpac, 2016;Macaro & Tian, 2015;Simasiku, Kasanda, & Smit, 2015;Thompson & Harrison, 2014;Tian & Macaro, 2012). The most common aspects are as follows: the functions and practicality of teacher's CS, the reasons for classroom CS, and the classroom participants' attitudes to CS.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It needs to be reiterated that, in some studies, the non-glossed reading condition was not altogether realistic. If it is deemed necessary to add a gloss per every 20 or so running words in order to make the text comprehensible for a given learner group (e.g., Arpaci, 2016;Azari et al, 2012;Jacobs et al, 1994;Sadeghi & Ahmadi, 2012), then the flipside of the coin is that, WITHOUT the glosses, the text is probably not going to be comprehensible. A well-informed teacher would probably not choose such material for their students' unassisted reading in the first place.…”
Section: Matters Of Text Comprehensibilitymentioning
confidence: 99%
“…It is surprising in this regard, that information about the L2 glosses that were used is absent in most of the research reports (e.g., Arpaci, 2016;Ertürk, 2016;Farvardin & Biria, 2012;Jacobs et al, 1994;Rouhi & Mohebbi, 2012;Shiki, 2008;Taheri & Zade, 2014;Zarei & Hasani, 2011) while others provide just one or a couple of examples (e.g., Mitarai & Aizawa, 1999;Miyasako, 2002;Salehi & Naserieh, 2013). This makes it impossible to evaluate how clear to the study participants these L2 definitions were in comparison with the L1 glosses.…”
Section: L1 Versus L2 Glossesmentioning
confidence: 99%
See 1 more Smart Citation